Counter-cyclical Voting in the United Kingdom. - Bojar, Abel (Political Studies, 2017)
By extending the time-tested reward–punishment hypothesis in economic voting, this article argues that rational voters hold incumbents accountable for the macroeconomic policies they pursue rather than purely for the economic climate that prevails under their tenure. Building on this premise, I first put forward a theory where business cycle fluctuations realign relative fiscal preferences among income groups. This theory’s implications predict that the aggregate electoral response to fiscal decisions evolves in a counter-cyclical fashion. Using quarterly measures of vote intention shares of incumbent parties in the United Kingdom, I provide time-series evidence from a set of error correction models supporting this proposition: at times of low unemployment, the electorate punishes profligate incumbents; in deteriorating labour market conditions, however, they reward expansionary policies. The immediate electoral impact is non-significant across the models, and most of the estimated effect is spread out across subsequent quarters.